IMPLEMENTATION OF PJBL TO INCREASE ELEMENTARY SCHOOL STUDENTS' LEARNING ACTIVENESS - Nuristikomah, Anisah (Kopertis Region IV Jabar and Banten, 2024)
Activeness in learning material about caring for the environment for class II students at SD N Kedondong is still low. One of the factors causing this is the lack of optimal use of media and learning models to help students understand concepts in environmental care material. This is the background for researchers to conduct research with the aim of increasing learning activity while improving the learning process to care for the environment through the use of a project based learning model assisted by interactive media in class II students at SD N Kedondong. This research is a type of classroom action research with an iterative and continuous cycle model. The subjects in this research were class II students at SD N 1 Kedondong, totaling 17 students consisting of 10 male students and 7 female students. The object of this research is active learning about caring for the environment material. The instruments used are test questions, observation sheets and documentation. The data obtained was analyzed quantitatively descriptively. The results of the research show that there is an increase in the activeness of Indonesian language learning about caring for the environment for class II students through the use of a project based learning model assisted by interactive media. This can be seen from the increase in students' scores on the volume of space material before and after being given the action. The average value increased from pre-cycle to 50, cycle I to 58.82 and to cycle II to 71.18. The percentage of completion in the pre-cycle reached 41.18%, cycle I reached 64.71% and in cycle II reached 82.35%. From these results it can be seen that there is an increase in the average value from pre-cycle to cycle II of 21.18. Apart from that, the quality of the learning process also increases. The increase in teacher activity from cycle I was 76% to 92% in cycle II with a very good category. The increase in student activity from cycle I was 71% to 91% in cycle II with a very good category.